2015
DOI: 10.1021/jacs.5b06794
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Lewis Pairs

Abstract: The articulation of the notion of "frustrated Lewis pairs" (FLPs), which emerged from the discovery that H2 can be reversibly activated by combinations of sterically encumbered Lewis acids and bases, has prompted a great deal of recent activity. Perhaps the most remarkable consequence has been the development of FLP catalysts for the hydrogenation of a range of organic substrates. In the past 9 years, the substrate scope has evolved from bulky polar species to include a wide range of unsaturated organic molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
538
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 985 publications
(544 citation statements)
references
References 206 publications
5
538
0
1
Order By: Relevance
“…For instance, the components of the couple t-Bu 3 P/B(C 6 F 5 ) 3 pair add to CO 2 at ambient temperature in bromobenzene with P-C and O-B bond formation, yielding the product t-Bu 3 P-C(O)O-B(C 6 F 5 ) 3 (Scheme 3) [96,97]. An analogous behavior was also observed with the intramolecular frustrated Lewis pair (C 6 H 2 Me 3 ) 2 PCH 2 CH 2 B(C 6 F 5 ) 2 .…”
Section: Stabilized By An External O-e Interaction (Where E Is a Diffmentioning
confidence: 99%
“…For instance, the components of the couple t-Bu 3 P/B(C 6 F 5 ) 3 pair add to CO 2 at ambient temperature in bromobenzene with P-C and O-B bond formation, yielding the product t-Bu 3 P-C(O)O-B(C 6 F 5 ) 3 (Scheme 3) [96,97]. An analogous behavior was also observed with the intramolecular frustrated Lewis pair (C 6 H 2 Me 3 ) 2 PCH 2 CH 2 B(C 6 F 5 ) 2 .…”
Section: Stabilized By An External O-e Interaction (Where E Is a Diffmentioning
confidence: 99%
“…Although some previous observations already suggested that cooperativity between Lewis pairs could promote metal-free transformations, notably for hydrosilylation [7], it is the use of FLPs for molecular hydrogen activation that led to a surge in research in this field [8][9]. Since, FLPs have been shown to activate many small molecules in addition to being active catalysts in reductive transformations [10][11][12]. The activation of substrates like H2 by transition metal complexes occurs generally by the transfer of electrons from the bond to be cleaved to the LUMO of the metal complex while electrons from the HOMO, either associated with the d orbitals or a ligand in the coordination sphere, are transferred to the anti-bonding orbital (Scheme 1A).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen activation by either transition metal complexes or metal-based heterogeneous catalysts have been well developed and successfully applied for various reactions4. Recently, frustrated Lewis pairs (FLPs), Lewis acids and bases that are sterically prevented from interaction to form Lewis acid–base adjuncts, can efficiently and cooperatively activate many small molecules (for example, H 2 , CO 2 , and NO) and even strong C–H bond for important catalytic reactions including hydrogenation, hydroamination and carbon dioxide reduction5678910111213141516171819202122232425.…”
mentioning
confidence: 99%